Distance Learning Implementation Model In Non-Formal Education - Irfansyah Bayu Putra Pamungkas; Arie Susanty (Southeast Asian Journal on Open and Distance Learning, 2025)
Distance learning has become an important solution to improve access to education, especially in non-formal education that serves as a complement or substitute for formal education. Non-formal education provides flexibility for learners who face economic, geographical or other constraints in accessing formal education. This research focuses on the development and implementation of the distance learning model at SPNF SKB Bukittinggi City using the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). The analysis stage identified institutional collaboration needs, subject mapping, and digital module development. The design stage finalised the learning content and model framework. In the development stage, workshops are conducted to build learning strategies and modules uploaded to the Learning Management System (LMS) platform. Implementation was conducted through field tests, and the feasibility of the model was evaluated. The results showed challenges, such as limited competence of educators in using the LMS and infrastructure issues. However, this study confirms the potential of distance learning in expanding access to education and supporting lifelong learning. Recommendations include continuous training and infrastructure improvements for the sustainability of this model.